Rural financial intermediation and poverty reduction in Ghana: A micro-level analysis - Michael Danquah; Abdul Malik Iddrisu; Williams Ohemeng; Alfred Barimah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The financial sector in rural areas, where most of the poor people in sub-Saharan Africa are found, has transformed massively in recent times, notably through the increased penetration of several types of rural financial intermediaries in addition to rural and community banks and microfinance institutions. Using recent household survey data, we ascertain the access of rural populations to various types of financial services, and the influence of rural financial intermediation on poverty reduction, in Ghana. By accounting for the potential endogeneity of access to financial services, we show that rural households with access to basic financial services are significantly more likely to be non-poor than those without such access. In order to more sustainably tackle the goal, highlighted in the Sustainable Development Goals, of eliminating global hunger or extreme poverty, the poor must be allowed to obtain meaningful access to financial services through the design of efficient pro-poor financial products.
Keywords: G21; I31; I32; 330; rural financial intermediation; poverty reduction; welfare; financial inclusion; Ghana